Biocontrol of citrus fungal pathogens by lipopeptides produced by Bacillus velezensis TZ01 - An, Baoju; Du, Danchao; Huang, Zhendong; Pu, Zhanxu; Lv, Jia; Zhu, Li; Liu, Shunmin; Zhang, Liping; Chen, Guoqing; Lu, Lianming (Frontiers in Microbiology, 2024)
Citrus diseases caused by fungal pathogens drastically decreased the yield and quality of citrus fruits, leading to huge economic losses. Given the threats of chemical pesticides on the environment and human health, biocontrol agents have received considerable attention worldwide as ecofriendly and sustainable alternative to chemical fungicides. In the present study, we isolated a Bacillus velezensis strain TZ01 with potent antagonistic effect against three citrus pathogenic fungi: Diaporthe citri, Colletotrichum gloeosporioides and Alternaria alternata. The culture supernatant of this strain exhibited remarkable antifungal activity on potato dextrose agar plates and detached leaves of five citrus varieties. Treatment with TZ01 culture supernatant obviously affected the hyphal morphology and caused nucleic acid leakage. The crude lipopeptides (LPs) extracted from the culture supernatant were found as the major active ingredients, and could maintain the activity under a wide range of temperature and pH and ultraviolet radiation. Furthermore, the type of LPs, produced in vitro, were explored. Whole-genome sequencing of TZ01 revealed secondary metabolite gene clusters encoding synthetases for non-ribosomal peptides and polyketide production, and gene clusters responsible for the synthesis of three important LPs (surfactin, iturin, and fengycin) were identified in the genome. The liquid chromatography-mass spectrometry analysis confirmed the presence of various homologs of surfactin A, bacillomycin D, and fengycin A in the extracted LPs. Taken together, these results contribute to the possible biocontrol mechanisms of B. velezensis strain TZ01, as well as providing a promising new candidate strain as a biological control agent for controlling citrus fungal pathogens.